2014
DOI: 10.1159/000360395
|View full text |Cite
|
Sign up to set email alerts
|

Acinic Cell Carcinoma of the Salivary Gland with Metastatic Spread to the Pancreas

Abstract: Metastatic disease to the pancreas is rare among solid tumors and has not been well described for salivary cancers. We report a patient who developed an isolated metastatic lesion in the pancreas from acinic cell carcinoma of the salivary gland, presenting as acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…26,27 Despite its well-documented indolent behavior, cases with aggressive behavior and metastasis are well documented. [28][29][30] ACC is best managed by excision with clear surgical margins via superficial lobectomy or total gland removal. Biron et al 26 suggested that the histological grade can better predict survival when compared with the TNM system, although this suggestion has been disputed.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Despite its well-documented indolent behavior, cases with aggressive behavior and metastasis are well documented. [28][29][30] ACC is best managed by excision with clear surgical margins via superficial lobectomy or total gland removal. Biron et al 26 suggested that the histological grade can better predict survival when compared with the TNM system, although this suggestion has been disputed.…”
Section: Discussionmentioning
confidence: 99%